An Outpatient Management Protocol for Emergency Department Patients With a Newly Diagnosed Lower Extremity Deep Venous Thrombosis. Issue 3 (September 2016) - Barrett, Tyler W.; Wrenn, Keith D.; Slovis, Corey M.; Jones, Ian D.; Wright, Patty W.; Self, Wesley H.; Russ, Stephan; Collins, Sean P.; Ward, Michael J.; Felbinger, Matthew; Atchison, Leanne; Beckman, Joshua A.
Abstract : Supplemental Digital Content is available in the text.